Ways to improve the forms and methods of increasing the competitiveness of leasing companies in Russia - A. A. Tilov (Управление)
The relevance of the study is determined by the need for a theoretical justification and development of proposals to improve the forms and methods of increasing the competitiveness of leasing companies in the current environment. In this regard, the problems in the Russian leasing services market and the causes of their occurrence have been analyzed in the article, the main trends of its development have been defined. The main areas of increasing the competitiveness of leasing companies in Russia have been designated and specific ways of development of these areas are proposed.The proposals to improve the functional management structure of leasing companies, to optimize the way they finance their activities, to improve price policy, have been considered in detail and developed in the article. Opportunities for implementation and development of risk management, expansion of the range of leasing services have been reviewed. Issues related to the state support of the leasing industry have been highlighted and considered by a separate aspect.Some of the risks of leasing companies associated with the activities of the leasing recipient organization especially have been highlighted. These include the risks of non-payment or late payment of lease payments, non-return of the leasing item, the risk of insolvency of the leasing recipient. And in this regard, ways of reducing these risks by conducting a comprehensive analysis of the leasing capacity in terms of the implementation of the planned project using all possible methods and tools of financial analysis have been determined.The methodological basis for this paper were modern scientific methods of research, including: the method of system analysis, methods of analogies, comparative analysis, expert methods, rating analysis, structural-functional and regulatory approaches.The results of the study were specific forms and methods to increase the competitiveness of leasing companies and improve their efficiency.